2004
DOI: 10.1074/jbc.m400283200
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Defects in Functional Interactions of Mitochondrial DNA Polymerase and DNA-binding Mutants of Single-stranded DNA-binding Protein

Abstract: Mitochondrial biogenesis is a key process in animal cell proliferation, and mtDNA replication is an essential component of that process. Whereas a large number of proteins participate in multi-component replication machines in bacterial and nuclear systems, a minimal set of essential proteins are likely involved in the mtDNA replication process (1). We have demonstrated functional interactions between the two-subunit Drosophila mitochondrial DNA polymerase (pol ␥) 1 and the homotetrameric mitochondrial single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Together with mitochondrial DNA helicase (also known as Twinkle) and the mitochondrial replicase, Pol ␥, it reconstitutes a minimal replisome for human mitochondria (2). Knockdown of mtSSB in human HeLa cells results in reduction of mitochondrial DNA (mtDNA) copy number due to a decrease in mtDNA synthesis (3), as was reported earlier for Drosophila Schneider cells in culture (4). Moreover, lopo mutants of Drosophila melanogaster in which mtSSB is absent die at an early stage in development, concomitant with the complete loss of mtDNA and respiratory capacity (5).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Together with mitochondrial DNA helicase (also known as Twinkle) and the mitochondrial replicase, Pol ␥, it reconstitutes a minimal replisome for human mitochondria (2). Knockdown of mtSSB in human HeLa cells results in reduction of mitochondrial DNA (mtDNA) copy number due to a decrease in mtDNA synthesis (3), as was reported earlier for Drosophila Schneider cells in culture (4). Moreover, lopo mutants of Drosophila melanogaster in which mtSSB is absent die at an early stage in development, concomitant with the complete loss of mtDNA and respiratory capacity (5).…”
mentioning
confidence: 74%
“…The presence of mtSSB 4 is a hallmark of replicating mitochondrial nucleoids (1). Together with mitochondrial DNA helicase (also known as Twinkle) and the mitochondrial replicase, Pol ␥, it reconstitutes a minimal replisome for human mitochondria (2).…”
mentioning
confidence: 99%
“…In addition, human mtSSB (HsmtSSB) stimulates stranddisplacement DNA synthesis promoted by the combined action of the human pol ␥ (Hspol ␥) and HsmtDNA helicase (2). In vivo, absence or depletion of mtSSB protein causes reduction of mtDNA copy number in Drosophila and human cells in culture (6,7), and lethality at the third larval stage in developing D. melanogaster (8). Although mtSSB mutations have not thus far been documented in association with human diseases, as is the case for the genes encoding pol ␥ and mtDNA helicase, a recent report shows a correlation between the levels of mtSSB protein, mtDNA copy number and the aggressiveness of human osteosarcoma cells, suggesting a link between mtDNA replication and cancer progression (9).…”
Section: Replication Of Animal Mitochondrial Dna (Mtdna)mentioning
confidence: 99%
“…Mitochondria also play essential roles in controlling cell viability and proliferation (1,2). A large number of studies have shown the essential roles of mitochondria in development and differentiation (3,4).…”
mentioning
confidence: 99%